(untitled) (Journal of the College of Basic Education, 2022)
The educators in recent years give great interest for activates which makes the student the axis of teaching and learning processes . From this reality the researcher decided to apply professed learning method by using learning aid methods as they are new techniques that are applied in institute of teachers in order to develop teachers learning levels in one of gymnastic skills which is Jumping on Jump stage and learn vocational school students capability to benefit from apply professed method in : Prepare learning environment through assents learning instrument that integrate with each other by computer. Learn in flounce of these instruments in developing technical performance of Jumping skills. Learn the differences in performance level before and after application. The researcher used experimental method. The research sample were choose from the first year student in teachers preparing institute. Karkh Directorate – second – sport Education numbered (55) student. They were selected by intentional method after dismissing the students who were absent from test and failed student. The number become (20) students in first learning year two equal groups randomly into experimental group and control group (10) students in each group. The researcher gave four learning units distributed as two learning unites each week the period of each unit (90) minutes through the subject teacher.